Recent Mössbauer studies on NiFe2O4 and Ni(Zn)Fe2O4 Ferrites (2022)
RESUMEN: We present recent results on the Mössbauer studies of NiFe2O4 and of Ni1-xZnxFe2O4 (x = 0.0, 0.2, 0.4, 0.6, 0.8 and 1.0) ferrites, which were synthesized by high-energy mechanical milling and by solid-state reaction methods. This work is mainly motivated by the accurate determination of the cation distribution in Ni and in Ni-Zn ferrites using the simple room temperature Mössbauer spectrometry. This calculation is known to be very important, because it determines the physicochemical properties of the ferrites. For the cation distribution, we determined the room-temperature recoilless f-factors ratio of the Fe3+ cations at octahedral [B] and tetrahedral (A) sites for NiFe2O4 by using formulas proposed by us. For that purpose, we first explore different procedures of synthesis based on the high-energy mechanical milling [1] and on the solid-state reaction [2] methods of stoichiometric mixtures of nickel oxide and hematite. The most pure, crystalline and with large grain-size sample was then used for the determination of the fB/fA ratio, which was found to be equal to 1.09 ± 0.01 [3]. This value differed from the normally used value of 0.94. Afterwards, we used it to calculate the cation distribution in Ni1-xZnxFe2O4 ferrites [4]. The Zn content at tetrahedral sites were also calculated from the intensities of the A1g Raman bands and from the intensity ratio of certain Bragg peaks (I(2 2 0)/I(4 4 0) and I(4 0 0)/I(2 2 0)) in the XRD patterns [5]. The values were compared considering the different approximations required by each technique.